Endothelin-1 induced hypertrophic effect in neonatal rat cardiomyocytes: Involvement of Na+/H+ and Na+/Ca2+ exchangers - Dulce, Raul (2006)
Endothelin-1 (ET-1) is a potent agonist of cell growth that also stimulates Na+/H+ exchanger isoform 1 (NHE-1) activity. It was hypothesized that the increase in intracellular Na+ ([Na+]i) mediated by NHE-1 activity may induce the reverse mode of Na+/Ca2+ exchanger (NCXrev) increasing intracellular Ca2+ ([Ca2+]i) which in turn will induce hypertrophy. The objective of this work was to test whether the inhibition of NHE-1 or NCXrev prevents ET-1 induced hypertrophy in neonatal rat cardiomyocytes (NRVMs). NRVMs were cultured (24 h) in the absence (control) and presence of 5 nmol/L ET-1 alone, or combined with 1 μmol/L HOE 642 or 5 μmol/L KB-R7943. Cell surface area, 3H-phenylalanine incorporation and atrial natriuretic factor (ANF) mRNA expression were increased to 131 ± 3, 220 ± 12 and 190 ± 25% of control, respectively (P < 0.05) by ET-1. [Na+]i and total [Ca2+]i were higher (8.1 ± 1.2 mmol/L and 636 ± 117 nmol/L, respectively) in ET-1-treated than in control NRVMs (4.2 ± 1.3 and 346 ± 85, respectively, P < 0.05), effects that were cancelled by NHE-1 inhibition with HOE 642. The rise in [Ca2+]i induced by extracellular Na+ removal (NCXrev) was higher in ET-1-treated than in control NRVMs and the effect was prevented by co-treatment with HOE 642 or KB-R7943 (NCXrev inhibitor). The ET-1-induced increase in cell area, ANF mRNA expression and 3H-phenylalanine incorporation in ET-1-treated NRVM were decreased by NHE-1 or NCXrev inhibition. Our results provide the first evidence that NCXrev is, secondarily to NHE-1 activation, involved in ET-1-induced hypertrophy in NRVMs.